2019
DOI: 10.1002/iub.2211
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and exosomes: Small molecules with big actions in multiple myeloma pathogenesis

Abstract: Multiple myeloma (MM), an incurable hematologic malignancy of plasma cells increasing in the bone marrow (BM), has a complex microenvironment made to support proliferation, survival, and drug resistance of tumor cells. MicroRNAs (miRNAs), short non‐coding RNAs regulating genes expression at posttranscriptional level, have been indicated to be functionally deregulated or abnormally expressed in MM cells. Moreover, by means of miRNAs, tumor microenvironment also modulates the function of MM cells. Consistently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 112 publications
(155 reference statements)
0
32
0
Order By: Relevance
“…Although some miRNAs can interact with Ago to bind their target mRNA inside the cell, others must be transported to MVBs via RNA-binding proteins (RBPs) and finally loaded into exosomes and secreted from the plasma membrane ( Fig. 2 ) [17]. Evaluation of the exosomal miRNA profile derived from cardiac fibroblasts showed high amounts of various miRNA passenger strands [34].…”
Section: Exosomal Micrornasmentioning
confidence: 99%
“…Although some miRNAs can interact with Ago to bind their target mRNA inside the cell, others must be transported to MVBs via RNA-binding proteins (RBPs) and finally loaded into exosomes and secreted from the plasma membrane ( Fig. 2 ) [17]. Evaluation of the exosomal miRNA profile derived from cardiac fibroblasts showed high amounts of various miRNA passenger strands [34].…”
Section: Exosomal Micrornasmentioning
confidence: 99%
“…Numerous observations indicate that EVs play a crucial role in MM pathogenesis [12,13] by affecting endothelial cell functions [14][15][16][17], enhancing tumor cell proliferation [18], and promoting immunosuppression [14,19]. In addition, EVs that contain miRNAs may be an important means of cell-cell communication within the MM tumor microenvironment [20]. Recent studies have shown that MM cell-derived EVs play a relevant functional role in activating osteoclast differentiation [21][22][23] and that the presence of the EGFR ligand amphiregulin is partially responsible for OC activation [21].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are notoriously involved in PD pathogenesis, and can be packaged in exosomes. Exosomes and miRNAs form a network that, both individually and synergistically, participates in the pathogenesis of PD among several other diseases (Mirzaei et al, 2017;Li et al, 2018;Saeedi Borujeni et al, 2018;Pourhanifeh et al, 2019).…”
Section: Micrornas In Exosomes Involved In Pd Pathogenesismentioning
confidence: 99%